Comparison of Deodorizing Properties of Several Typical Fibers (Journal of Fiber Bioengineering and Informatics, 2018)
Socks and underwear emit unpleasant odor, especially after they have been worn for long durationsunder certain conditions. This paper discusses the deodorizing properties of several typical fibers suchas deodorizing acrylic, wool, line, cotton, Modal® and polyester fibers by instrumental testing. The odorfrom the socks made of these fibers after a one-day wear in summer is further evaluated by three testersusing a human olfactory test. The molecular structure of the deodorizing acrylic fiber was confirmedby infrared spectroscopy. In terms of the deodorizing property of the various fibers with respect toammonia, it is found that the deodorizing acrylic fiber had the best performance. This is attributedto the carboxyl groups in its molecular structure. Wool, Modal®, cotton, and linen fibers were worsein turn; polyester fibers had the worst performance. The absorption of acetic acid by wool, linen, anddeodorizing acrylic fibers was better, followed by Modal® and cotton fibers. The polyester fibers, onceagain, had the worst performance. Thicker socks diffuse less odor than thinner socks made from the samefibers. The results of chemical analysis and sensory analysis show that the deodorizing performance ofdeodorizing acrylic fibers is superior.